(untitled) (INSTITUTIO : Jurnal Pendidikan Agama Kristen, 2025)
Abstract: This study aims to identify and describe the role of Christian Religious Education in developing soft skills among Generation Alpha. The soft skills in question include communication, empathy, leadership, and social abilities that are essential for everyday life. The research employs a qualitative approach using a literature study method, involving analysis of relevant literature and sources on Christian Religious Education and the development of soft skills in Generation Alpha. The findings indicate that Christian Religious Education can serve as an effective medium for fostering soft skills in Generation Alpha. Values such as love, forgiveness, respect, character education, and social practice taught in Christian Religious Education have a positive impact on the interpersonal abilities of Generation Alpha children. In conclusion, Christian Religious Education plays a significant role in shaping character and soft skills in Generation Alpha. Therefore, Christian schools and other educational institutions can utilize the Christian Religious Education curriculum to cultivate soft skills that are beneficial for the social and professional lives of Generation Alpha. Keywords: Development; Soft skills; Generation Alpha; Christian Religious Education